2018
DOI: 10.1136/jclinpath-2018-205194
|View full text |Cite
|
Sign up to set email alerts
|

PON1gene polymorphisms in patients with chronic obstructive pulmonary disease

Abstract: Higher frequency of TT genotype and T allele could contribute to the observed reduction of PON1 activity in patients with COPD. T allele and TT genotype are associated with COPD, and the -108C>T polymorphism could be a potential predictor of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Of the 119 initially identified articles, 100 articles were excluded after screening of titles and abstracts. After screening of full-texts, six studies were excluded because six studies did not focus on PON1 activity of patients with COPD [ 22 , 23 , 24 , 25 , 26 , 27 ]. One study [ 28 ] was excluded because it included the same population as another study [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 119 initially identified articles, 100 articles were excluded after screening of titles and abstracts. After screening of full-texts, six studies were excluded because six studies did not focus on PON1 activity of patients with COPD [ 22 , 23 , 24 , 25 , 26 , 27 ]. One study [ 28 ] was excluded because it included the same population as another study [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lada et al reported that patients with COPD had lower PON1 activity compared with healthy subjects, 45 and they found that PON1 polymorphism could contribute to the reduction of PON1 activity in patients with COPD. 46 SEPTIN2 is a member of a highly conserved GTPase family. It was revealed that SEPTIN2 fundamentally regulated airway epithelial barrier function in response to pathological luminal stimuli by altering cortical actin expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the lung, PON1 has been detected through immunohistochemical evidence in type 1 pneumocytes, but its physiological role in the context of lung antioxidant activity has not yet been described [ 97 ]. However, there are a few publications on the role of PON1 activity in patients with asthma and COPD [ 98 , 99 , 100 ] and on its impact on lung cancer behavior and progression by antioxidative function and controlled ROS accumulation [ 101 ].…”
Section: Diminished Antioxidant Defensesmentioning
confidence: 99%